2022
DOI: 10.3389/fnbeh.2022.732375
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Drinking Under Limited-Access Procedures During Mature Adulthood Accelerates the Onset of Cognitive Impairment in Mice

Abstract: A history of heavy drinking increases vulnerability to, and the severity of, Alzheimer’s disease (AD) and related dementias, with alcohol use disorder identified as the strongest modifiable risk factor for early-onset dementia. Heavy drinking has increased markedly in women over the past 10 years, particularly in mature adult women during the coronavirus (COVID-19) pandemic. This is concerning as women are more sensitive to many alcohol-related disease states, including AD and related dementias. Herein, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 127 publications
2
32
1
Order By: Relevance
“…Recent translational work highlights sex differences in the interaction of EtOH with Alzheimer’s disease-related pathology. EtOH exposure caused greater cognitive impairment in female than male “middle aged” (ages 6 to 9 months) wild-type C57BL/6J mice, 390 which was associated with an increase in hippocampal amyloid levels. 391 In mice with abnormal tau deposition (i.e., PS19 model with the T34 tau isoform), 16 weeks of intermittent access to water containing 20% EtOH increased the excitability of the locus coeruleus more in female than male mice.…”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“…Recent translational work highlights sex differences in the interaction of EtOH with Alzheimer’s disease-related pathology. EtOH exposure caused greater cognitive impairment in female than male “middle aged” (ages 6 to 9 months) wild-type C57BL/6J mice, 390 which was associated with an increase in hippocampal amyloid levels. 391 In mice with abnormal tau deposition (i.e., PS19 model with the T34 tau isoform), 16 weeks of intermittent access to water containing 20% EtOH increased the excitability of the locus coeruleus more in female than male mice.…”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“…Recent data show robust increase in the prevalence of excessive alcohol drinking among women ( 8 12 ). Women exhibit more sensitivity to alcohol; with sooner progression to alcohol-related diseases at less drinking levels compared to men ( 13 15 ). The deleterious effects of excessive alcohol drinking on cognitive functions are well documented ( 16 19 ) specifically in women ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy alcohol drinking (> 14 drinks/week) significantly increases the likelihood of developing dementia [ 1 4 ] and reduces the age of dementia-onset in both humans [ 5 ] and laboratory rodents [e.g., 6 8 ]. In fact, alcohol use disorders ( AUDs ) account for approximately 60% of early-onset dementia cases and thus are the strongest modifiable risk factor for this condition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aligning with these data, studies of wild-type, inbred, C57BL/6 ( B6 ) mice also indicate that alcohol can induce microglial activation [ 22 ] and upregulate the expression of ADRD-related genes in brain [e.g., 7,23,24]. In terms of behavior, a history of binge-drinking by adolescent B6 mice is reported to induce signs of cognitive impairment when assessed in later adulthood [ 25 ] and we recently showed that binge-drinking by B6 mice during mature adulthood (i.e., 6 months of age; [ 26 ]) accelerates cognitive decline to a level comparable to aged (18 month-old) animals [ 8 ]. Although we did not detect a sex difference in age-related cognitive decline in our recent study, in two replicate studies of B6 mice, mature adult female alcohol-drinking mice exhibited more signs of cognitive impairment than their male counterparts [ 8 ], arguing that mature adult females are more vulnerable than males to an alcohol-induced acceleration of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation